Do investors care about offshoring? : The impact of offshoring decisions and related events on firms’ value. - Kukula, Jakub (2020)
The use of offshore financial structures has become a popular method to avoid taxes, especially for the multinational corporations. This thesis focuses on the effect of different types of information about involvement in tax avoidance on firms’ value. The effect of the new information about firms’ involvement in tax avoidance is evaluated by the event study technique in five case studies each focusing on different type of event. Only in one case study the negative abnormal return caused by the information announcement was confirmed as statistically significant. However, even in that case the new information had a very little effect on firms’ value. Therefore, this study concludes that even though tax avoidance practices are heavily discussed topic in these days, in most cases there is no significant negative reaction of investors to new information about firms’ involvement in tax avoidance.